Mechanical properties of sand modified resins used for bonding CFRP to concrete substrates - Abdulla, A.I.; Razak, H.A.; Salih, Y.A.; Ali, M.I. (Elsevier, 2016)
This study is an experimental investigation into the properties of adhesive before and after mixing with fine sand, and its behavior on reinforced concrete beams strengthened by CFRP to show the effects of modified adhesive on load-carrying capacity, ductility, stiffness and failure mode of the reinforced concrete beams. Compressive strength, flexural strength and the effect of high temperature on these properties were the focus of the current study in order to prove the efficiency of adding fine sand to improve adhesive properties and reduce cost. Based on the compressive and flexural tests, results indicated that the addition of sand to the adhesive improved its mechanical properties when sand is 50% of the total weight of the adhesive. However, its effect on the modulus of elasticity is minimal. Using adhesive with fine sand increased the ultimate load bearing capacity, ductility, stiffness and toughness of the reinforced concrete beams strengthened by CFRP. The ratio of the fine sand to the adhesive equal to 1 is considered the best in terms of the cost reduction, maintaining workability, as well as maintaining the mechanical properties. Lastly, the use of fine sand with adhesive ensured a significant reduction in the cost of the adhesive and increased the adhesive resistance to temperature.